Manufacturing Engineering Select Proceedings of CPIE 2018 - Sharma, Vishal S.; Dixit, Uday S.; Alba-Baena, Noe (Lecture Notes on Multidisciplinary Industrial Engineering, 2019)
This book presents selected proceedings of the International Conference on Production and Industrial Engineering (CPIE) 2018. Focusing on recent developments in the field of production and manufacturing engineering, it provides solutions to wide-ranging contemporary problems in manufacturing engineering and other allied areas using analytical models and the latest numerical approaches. The topics covered in this book include conventional and non conventional machining, casting, welding, materials and processing. As such it is useful to academics, researchers and practitioners working in the field of manufacturing and production engineering.